Progreso médico: encefalitis autoinmune contra el receptor de N-metil-D-aspartato asociada a teratomas - Cordero Morelo, Isabela (2019)
Autoimmune encephalitis against the N-methyl-D-aspartate receptor (NMDA-R) is a newly discovered disease that occurs mainly in young women. It is characterized by the presence of autoantibodies against NMDA receptor, specifically against the GluN1 subunit; which generates psychotic symptoms, movement disorders, autonomic dysfunction and even coma. About 50% of patients present ovarian teratoma when completing the studies. This disease is reversible and treatable, therefore diagnosis and treatment are essential. The first line of treatment includes steroids, intravenous G immunoglobulin or plasmapheresis. The second line consists of rituximab and cyclophosphamide. In addition, in the cases where a tumor is documented, the extirpation of it is considered fundamental.